(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The traditional campus recruitment process in many educational institutions suffers from inefficiencies such as manual record management, fragmented communication, and limited analytical capabilities, resulting in delays and reduced placement effectiveness. This paper proposes a high-performance web-based Campus Recruitment System designed to automate and streamline placement management through a role-based architecture comprising Admin, Company, and Student portals. The system is implemented using a scalable three-tier architecture consisting of a responsive presentation layer (HTML, CSS, JavaScript, Bootstrap), an application layer developed in PHP for authentication and role-based access control, and a MySQL relational database structured in Third Normal Form (3NF) to ensure data integrity and optimized query performance. Security mechanisms including password hashing and input validation are integrated to enhance system reliability. Experimental evaluation demonstrates improved operational efficiency, reducing administrative workload by approximately 40% and achieving faster response times under concurrent access conditions. The proposed solution provides a transparent, scalable, and efficient ecosystem for managing campus recruitment processes.